SYSTEMATIC LITERATURE REVIEW: DEVELOPMENT OF AGRICULTURAL MANAGEMENT ON JERUK KEPROK FARMERS IN CENTRAL ACEH REGENCY, GAYO HIGHLANDS - Haryadi Sarjono; Della Amelinda Putri (Syarif Hidayatullah State Islamic University Jakarta, 2025)
This study aims to determine the tangerine (orange) farmers in Central Aceh District, Gayo Highlands. The cultivation of Orange Keprok in the Gayo highlands holds strong agribusiness potential due to a suitable agroclimate, available farmland, and growing national market demand. This research uses a Systematic Literature Review to analyze relevant literature and several case studies as a development Tangerine cultivation in Central Aceh District, specifically in the Gayo Highlands. 9 literatures were evaluated from Google Scholar based on keywords (